A simple experiment to show photodynamic inactivation of bacteria on surfaces - Caminos, Daniel Alberto (2007)
New suitable approaches were investigated to visualize the photodynamic inactivation (PDI) of bacteria immobilized on agar surfaces. The PDI capacities of a cationic [5,10,15,20-tetra(4-N,N,N-trimethylammoniumphenyl)porphyrin] and an anionic [5,10,15,20-tetra(4-sulphonatophenyl)porphyrin] photosensitizers were analyzed on a typical Gram-negative bacterium Escherichia coli following two procedures. In experiment I, the E. coli cells were grown as lawn on agar surface containing the sensitizers spread in a small area (10 nmol in ~0.6 cm2). After irradiation with visible light (10 min, 90 mW/cm2), no cells were grown in the area containing the cationic porphyrin. In experiment II, small colonies (~2 mm diameter) of E. coli on agar were treaded with a solution of sensitizer (10 nmol) and irradiated with visible light for 3 h. Overnight incubation at 37ºC shows that a growth delay of E. coli colonies treated with the cationic photosensitizer. In contrast, the anionic porphyrin did not produce appreciable photodamage. These experiments could be used in either an undergraduate project for natural science advance students or for postgraduate practical training course. This methodology illustrates the application of PDI to treat bacteria growing as localized foci of infection.